Pelatihan Pengelolaan Sumber Daya Manusia Di Era Digital Terkait Kepuasan Pelanggan Pada Umkm Resto Selera Sambal Cikarang Selatan - Rismawati, Rismawati; Markos, Aos; Rosanti, Vira Citra; Shahyatul, Intan Aissa (CV. ITTC INDONESIA, 2025)
The culinary industry is one of the sectors that continues to grow rapidly and has great potential in the economy, especially in Indonesia. Micro, Small, and Medium Enterprises (UMKM) in the restaurant sector play an important role in providing jobs and increasing the competitiveness of the local economy. Rujito (2022) According to him, UMKM are one type of business that has a lot of influence on the Indonesian economy, both from the number of businesses formed and the number of jobs created. The purpose of the research we conducted was to provide training on customer satisfaction surveys in the digital era by utilizing current technology. The research method we use is by questionnaires and direct interviews with UMKM owners and employees of Resto Selera Sambal. The results of the study show that digital-based human resource management training at UMKM Resto Selera Sambal has a positive impact on improving service quality and slow satisfaction.